How do Baitul Maal Wat Tamwil empower Micro, Small and Medium Enterprises amidst COVID-19 pandemic? A case of Indonesia - Ma'ruf, Aminudin; Elmi Nur Azizah; Jannah Arrum Sari (IAIN Surakarta, 2022)
During the COVID-19 pandemic, Baitul Maal Wat Tamwil (BMT) in Sukoharjo, a region of Indonesia is consistently contributing to the empowerment of Micro, Small and Medium Enterprises (MSMEs). Hence, how the BMT empowers the MSMEs is a worthy attribute to explore. The current study delves into an in-depth exploration on the strategies and policy innovations carried out by the BMTs as well as to analyse the impact or influence caused by the existence of these strategies. The method used in this research is field research with a qualitative approach. Data collection techniques were carried out through observation with interviews with various related parties. The results showed that the empowerment strategy carried out by BMT Dana Mulia and BMT Makmur Mandiri was by implementing a restructuring policy in an effort to maintain the stability of the institution's operations. Meanwhile, BMT Bina Ummah Sejahtera has tightened risk mitigation by making efforts to be more careful in conducting financing and deposit transactions, using online media and the three BMTs providing business assistance. The influences that arise with this strategy are providing ease of capital assistance during the COVID-19 pandemic, assisting business development of MSMEs, minimizing the risks faced by MSMEs, and encouraging the spirit of MSMEs in marketing their businesses.